WINTER AND SUMMER AS A REPRESENTATION OF EXILE IN RETURN TO TIPASA (1954) BY ALBERT CAMUS AND IN THE MIDST OF WINTER (2017), BY ISABEL ALLENDE - Athayde, Maria Vitoria de Almeida [UNESP]; Callipo, Daniela Mantarro [UNESP] (Univ Federal Juiz Fora, Campus Univ, 2023)
This article aims to analyze the epigraph taken from Return to Tipasa (1954), by Albert Camus, and inserted in the novel In the midst of winter (2017), by Isabel Allende, in order to investigate the intertextual and dialogical relationship that is established between the winter mentioned in the French-Algerian writer's essay and the one present in the Allendian novel, based on the character Lucia. Based on Bakhtin (2003), (2015), Kristeva (2012), Genette (2010) and Moraes Pinto (2003), we propose to investigate the dialogical relationships between the works and highlight the similarities and differences between them, in the with regard to the vision of winter present in them, through the concepts of comparative literature. The conclusion reached is that the epigraph used by Allende should not be ignored by the reader of the novel, since it works as an arrow that indicates the path to be followed for a deeper understanding of the narrative; that is, the reading of the Camusian tale
Keywords: Comparative Literature; Exile; Epigraph; Albert Camus; Isabel Allende